The Role of Blade Sinusoidal Tubercle Trailing Edge in a Centrifugal Pump with Low Specific Speed - Bowen Li; Xiaojun Li; Xiaoqi Jia; Feng Chen; Hua Fang (Processes, 2019)
Pressure pulsations may cause high-amplitude vibrations during the process of a centrifugal pump. The trailing edge shape of the blade has a critical influence on the pump’s pressure fluctuation and hydraulic characterization. In this paper, inspired by the humpback whale flipper, the authors research the impact of applying the sinusoidal tubercles to the blade suction side of the trailing edge. Numerical calculation and experiments are carried out to investigate the impact of the trailing edge shape on the pressure pulsations and performance of a centrifugal pump with low specific speed. Two designed impellers are tested, one is a sinusoidal tubercle trailing edge (STTE) impeller and the other is the original trailing edge (OTE) prototype. The detailed study indicates that the sinusoidal tubercle trailing edge (STTE) reduces pressure pulsation and enhances hydraulic performance. In the volute tongue region, the pressure pulsation amplitudes of STTE at fBPF decrease significantly. The STTE impeller also effectively changes the vortex structure and intensity in the blade trailing edge area. This investigation will be of great benefit to the optimal design of pumps.